2017
DOI: 10.1136/annrheumdis-2017-211623
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of lymphomas across different drug treatment groups in rheumatoid arthritis: a European registries collaborative project

Abstract: BackgroundLymphomas comprise a heterogeneous group of malignant diseases with highly variable prognosis. Rheumatoid arthritis (RA) is associated with a twofold increased risk of both Hodgkin’s lymphoma (HL) and non-Hodgkin’s lymphoma (NHL). It is unknown whether treatment with biologic disease-modifying antirheumatic drugs (bDMARDs) affect the risk of specific lymphoma subtypes.MethodsPatients never exposed to (bionaïve) or ever treated with bDMARDs from 12 European biologic registers were followed prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 30 publications
5
43
0
6
Order By: Relevance
“…Epstein‐Barr virus (EBV) positivity, a possible surrogate marker for immunosuppression, was evident in only 17% of cases . This finding was recently verified by a European registry study that included 124 997 patients with RA . Here, similar results were observed in lymphoma subtype, with no difference noted between patients treated with anti TNF and those who received biological disease modifying antirheumatic drugs (DMARDS) or bio‐naïve patients.…”
Section: Lymphoma Subtypes Biology and Clinical Prognosis In Ramentioning
confidence: 54%
See 1 more Smart Citation
“…Epstein‐Barr virus (EBV) positivity, a possible surrogate marker for immunosuppression, was evident in only 17% of cases . This finding was recently verified by a European registry study that included 124 997 patients with RA . Here, similar results were observed in lymphoma subtype, with no difference noted between patients treated with anti TNF and those who received biological disease modifying antirheumatic drugs (DMARDS) or bio‐naïve patients.…”
Section: Lymphoma Subtypes Biology and Clinical Prognosis In Ramentioning
confidence: 54%
“…Here, similar results were observed in lymphoma subtype, with no difference noted between patients treated with anti TNF and those who received biological disease modifying antirheumatic drugs (DMARDS) or bio‐naïve patients. Regardless of the type of treatment given for RA (anti‐TNF, MTX, or others), the most common lymphoma subtype was DLBCL, occurring in 249/533) 47%) of all lymphomas diagnosed …”
Section: Lymphoma Subtypes Biology and Clinical Prognosis In Ramentioning
confidence: 99%
“…45,46 Data also suggest that anti-TNF agents increase the risk of non-Hodgkin's lymphoma in patients with IBD. [47][48][49][50] However, other studies have suggested that the overall risk of lymphoma does not differ significantly from untreated patients and instead correlates with the degree of disease activity rather than therapy type. 51 Recent analyses of patients with RA found that the pooled odds ratio for developing a malignancy was 3.3 and the number needed for harm was 154 per additional malignancy, within a treatment period of 6-12 months.…”
Section: Limitations Of Parenteral Administration Of Anti-tnf Agentsmentioning
confidence: 99%
“…Similarly, there is evidence that there is a dose‐dependent risk of malignancy in patients with RA who were treated with anti‐TNF therapy . Data also suggest that anti‐TNF agents increase the risk of non‐Hodgkin's lymphoma in patients with IBD . However, other studies have suggested that the overall risk of lymphoma does not differ significantly from untreated patients and instead correlates with the degree of disease activity rather than therapy type .…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor , Controversy exists regarding the risk and prognosis of lymphomas during treatment with biologics . Risk evaluation must consider the underlying medical condition – as chronic inflammatory diseases are associated with an excess risk of lymphoma – and ongoing treatments (azathioprine, ciclosporin) .…”
Section: Cutaneous Lymphoma During Treatment With Biologics: Data Fromentioning
confidence: 99%